Circulating C-terminal peptides and polymers of alpha-1 antitrypsin as putative markers of pediatric Pi*ZZ liver disease - Katzer, David; Börner, Friedemann Robert; Weigert, Alexander; Held, Julia; Bagci, Soyhan; Ganschow, Rainer; Mielczarek, Pia; Machui, Alexander; Kiehntopf, Michael; Janciauskiene, Sabina (Frontiers in Pediatrics, 2025)
ObjectiveSevere Pi*ZZ alpha-1 antitrypsin (AAT) deficiency, caused by the Glu342Lys mutation in the SERPINA1 gene, resulting in protein misfolding and polymerization in hepatocytes, and proteotoxic stress which may lead to progressive liver injury. Although liver disease can appear in both childhood and adulthood, most children remain asymptomatic, but no reliable circulating biomarkers currently predict disease progression. In this exploratory study, we aim to assess C-terminal AAT peptides and AAT polymers as potential plasma markers of liver status in clinically stable Pi*ZZ children.MethodsPlasma from 20 Pi*ZZ children was analyzed by liquid chromatography–tandem mass spectrometry for nine C-terminal AAT peptides and by western blot for AAT polymers. Associations with liver enzymes, ursodeoxycholic acid use, age, and clinical severity scores were evaluated.ResultsPeptides C36, C37, and C42 were consistently detectable in plasma. C37 and C42 levels negatively correlated with age and positively with alanine aminotransferase; C42 additionally correlated with aspartate aminotransferase. Both C37 and C42 were reduced in children receiving ursodeoxycholic acid, whereas C36 showed no significant associations. Circulating AAT polymers correlated with γ-glutamyl transferase but not with alanine or aspartate aminotransferase. No correlations were observed between peptide and polymer levels.ConclusionPeptides C37 and C42 emerge as promising AAT-derived markers of hepatocellular status in stable Pi*ZZ children, while AAT polymers appear to reflect distinct features of cholestatic or hepatocellular stress. Together, these markers may support early risk stratification and therapeutic monitoring in pediatric AATD-related liver disease. Validation in larger, longitudinal cohorts is warranted to confirm their clinical utility.